Analisis Pengaruh Komposisi Kepemilikan Terhadap Manajemen Laba Pada Perusahaan Yang Terdaftar Di Bursa Efek Indonesia - Mardianto Mardianto; Khellystina Khellystina (Journal of Applied Accounting and Taxation, 2021)
This study aims to analyze the effect of ownership composition on earnings management in companies listed on the Indonesia Stock Exchange. This study method is quantitative research that emphasizes testing of variables through data in the form of numbers and analyzing data with statistical procedures. The population used in this study is the listed company from Indonesia Stock Exchange between 2016 – 2020 and for data testing tools using the SPSS 25 and Eviews 10. Ownership composition is represented by family ownership, institutional ownership, blockholder ownership, debt, firm size, return on equity and sales growth. The results of this study showed that debt is significantly positive on earnings management, sales growth is significant negative on earnings management. Meanwhile, family ownership, institutional ownership, blockholder ownership, firm size and return on equity show no significant results. All independent variables can explain the dependent variable by 31.45% based on the coefficient of determination test.